Shared Attention during Sight Translation, Sight Interpretation and Simultaneous Interpretation - Lambert, Sylvie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis study set out to determine the types of processing involved when subjects perform sight translation compared to both sight interpretation and simultaneous interpretation, but more specifically whether performance is enhanced or hindered by the visual presentation of the material to be interpreted. Results indicated that both sight translation and sight interpretation yielded significantly higher performance scores than simultaneous interpretation, indicating that the added feature of visual exposure to the message to be interpreted does not necessarily interfere with a subject’s already overloaded capacity to listen and speak simultaneously, but that in fact, it may even help the student’s performance. Pedagogically speaking, it is recommended that sight interpretation be included in any cognitive approach to a simultaneous-interpreter training program.